Both organic and integrated pest management of apple orchards maintain soil health as compared to a semi-natural reference system. (1st February 2022) - Daelemans, Robin; Hulsmans, Eva; Honnay, Olivier
Abstract: Growing concerns about the negative environmental impacts of agriculture have resulted in the increasing adoption of farming systems that try to reconcile crop production with environmental sustainability, such as organic farming. As organic farming refrains from using synthetic inputs, it heavenly relies on maintaining soil health. However, it is still poorly understood how organic management performs in terms of maintaining soil health in real commercial and heterogeneous farm settings as compared to conventional management, and especially as compared to a natural reference system. Here, we compared a set of soil health indicators among 24 commercial apple orchards that were either managed organically or conventionally using Integrated Pest Management (IPM) practices. In addition, we quantified the same indicators in 12 semi-natural grasslands as a benchmark to assess to what extent soil processes and functions have been degraded due to agricultural practices. As soil heath indicators, we quantified soil bulk density, organic matter content, organic carbon content, organic carbon stock, total nitrogen (N), potential heterotrophic respiration, potential net N mineralization, litter decomposition and litter stabilization, and we added the diversity of the herbaceous vegetation and the soil microbiome as covariates in our models. We found no differences between organic and IPM orchards, and neither of the farming systems showed evidence of impaired soil health compared to the semi-natural benchmark, with the exception of higher decomposition rates measured in both orchard types. We observed, however, high spatial variation in soil health between drive and crop rows within the orchards. Especially in the IPM orchards, crop rows showed impaired soil health compared to the adjacent drive rows, indicating that there is still opportunity to improve soil management in the IPM system. In addition, our results show that a considerable part of the variation in soil characteristics can be attributed to the study site, suggesting that both natural heterogeneity and personal management preferences by individual farmers are more important than the management system. Overall, and at least in terms of the soil variables measured in this study, our results suggest that perennial crop systems can be managed in a sustainable way, without jeopardizing soil health. Highlights: Similar soil health in organic and Integrated Pest Management orchards. High spatial variation in soil health within orchards. No impaired soil health in orchards compared to a semi-natural reference. Perennial crops can be managed without jeopardizing soil health.